Metabolizable Protein: 2. Requirements for Maintenance in Growing Saanen Goats - Souza, Anaiane P.; Vargas, Julián A. C.; Fernandes, Marcia H. M. R.; Almeida, Amélia K.; Resende, Kleber T.; Teixeira, Izabelle A. M. A. (Frontiers in Veterinary Science, 2021)
This study aimed to estimate the protein requirements for the maintenance of growing Saanen goats of different sexes from 5 to 45 kg of body weight (BW) using two methods and applying a meta-analysis. For this purpose, two datasets were used. One dataset was used to evaluate the effects of sex on the protein requirements for maintenance using the comparative slaughter technique. This dataset was composed of 185 individual records (80 intact males, 62 castrated males, and 43 females) from six studies. The other dataset was used to evaluate the effects of sex on the protein requirements for maintenance using the N balance method. This dataset was composed of 136 individual records (59 intact males, 43 castrated males, and 34 females) from six studies. All studies applied an experimental design that provided different levels of N intake and different levels of N retention, allowing the development of regression equations to predict the net protein requirement for maintenance (NPM) and the metabolizable protein (MP) requirements for maintenance (MPM) in Saanen goats. The efficiency of MP use for maintenance (kPM) was computed as NPM/MPM. The efficiency of MP use for gain (kPG) was calculated using the equation of daily protein retained against daily MP intake above maintenance. A meta-analysis was applied using the MIXED procedure of SAS, in which sex was considered a fixed effect, and blocks nested in the studies and goat sex were considered as random effects. The NPM did not differ between sexes, irrespective of the approach used. Using the comparative slaughter technique, the daily NPM estimated was 1.23 g/kg0.75 BW, while using the N balance technique was 3.18 g/kg0.75 BW for Saanen growing goats. The MPM estimated was 3.8 g/kg0.75 BW, the kPM was 0.33, and the kPG was 0.52. We observed the NPM using the comparative slaughter technique in growing Saanen goats is lower than those recommended by the current small ruminant feeding systems; on the other hand, the MPM was similar to previous reports by the feeding systems. Sex did not affect the protein requirements for maintenance and the efficiencies of use of metabolizable protein.